Size heterogeneity of prolactin secreted from and stored in the rat anterior pituitary gland in vitro. Issue 2 (February 1984) - Bentley, Andrew M.; Surowy, Teresa K.; Wallis, Michael
Abstract : The size heterogeneity of rat pituitary prolactin was investigated using anterior pituitary glands from female rats incubated in vitro and gel filtration on Sephadex G-100. Monomeric prolactin was preferentially secreted compared with dimeric and 'trimeric" material. When glands were incubated with dopamine, prolactin secretion was inhibited and the relative proportion of dimer in the gland (but not the medium) was decreased. Morphine sulphate reversed the effect of dopamine on prolactin secretion and on the proportion of prolactin in the gland that was in the dimeric form. The results suggest that monomeric prolactin is more readily secreted than dimer, and that dopamine decreases the production or stability of the dimer.